2017
DOI: 10.1007/s11356-017-9970-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of carbonaceous fractions in PM2.5 and PM10 over a typical industrial city in central China

Abstract: Aerosol samples of PM and PM were collected every 6 days from March 2012 to February 2013 in Huangshi, a typical industrial city in central China, to investigate the characteristics, relationships, and sources of carbonaceous species. The PM and PM samples were analyzed for organic carbon (OC), elemental carbon (EC), char, and soot using the thermal/optical reflectance (TOR) method following the IMPROVE_A protocol. PM and PM concentrations ranged from 29.37 to 501.43 μg m and from 50.42 to 330.07 μg m, with av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 56 publications
1
18
2
Order By: Relevance
“…To our knowledge, there are no existing studies that have investigated the relationship between air pollution and SGA in central China. Huangshi is an industrial city in central China, and its economic growth has been attributed to mining and metallurgy in recent years (Zhan et al 2017). Although the concentrations of air pollutants in Huangshi are lower than those in other industrial cities, such as Wuhan (Qian et al 2016), air pollution exposure in Huangshi is still relatively higher than the air quality guidelines (AQG) issued by the World Health Organization (WHO 2005).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are no existing studies that have investigated the relationship between air pollution and SGA in central China. Huangshi is an industrial city in central China, and its economic growth has been attributed to mining and metallurgy in recent years (Zhan et al 2017). Although the concentrations of air pollutants in Huangshi are lower than those in other industrial cities, such as Wuhan (Qian et al 2016), air pollution exposure in Huangshi is still relatively higher than the air quality guidelines (AQG) issued by the World Health Organization (WHO 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Soot contains dominant polycyclic aromatic hydrocarbons, compounds containing oxygen (furans, benzofurans, and phenols), and compounds containing aliphatic nitrogen (benzonitrile). 1,60,63,64 Several studies have been conducted in Southeast Asia, Indochina, and India on the emission of char-EC and soot-EC from different sources. The studies found that low (∼1) char-EC/soot-EC ratios indicate the fuel combustion of transportation sectors and burning of grass, whereas high char-EC/soot-EC ratios reflect wood combustion, particularly biomass burning by smoldering at low temperature, in the study areas.…”
Section: Introductionmentioning
confidence: 99%
“…1,55,70,71 Ratios ranging from <1 to 1.6 are observed for fresh traffic emissions, 1,70 whereas ratios between 1 and 2 have been reported for urban sources. Ratios ranging from 2 to 5 indicate a coal combustion origin 1,55 and are assumed to indicate the considerable contribution of secondary aerosol sources. 70 High OC/EC ratios are indicative of secondary origins and processes that are influenced drastically by the contribution of secondary organic aerosols to the OC fraction.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies of VOCs in China have focused on developed megacities. Researches on particulate matters for developing areas in China had been started [17][18][19], while for VOCs and O 3 control, data and studies are still leaving limited and far from sufficient [20].…”
Section: Introductionmentioning
confidence: 99%